2009
DOI: 10.1002/ejic.200800913
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Analysis of β‐Lactam‐Containing Ferrocene Peptides

Abstract: The homochiral 3-amino-1-(4-methoxyphenyl)-4-phenyl-β-lactam (ϵ Alm) was conjugated with Boc-Ala to give AlaAlm (9) after Boc deprotection (Boc = tert-butoxycarbonyl, Ala = alanine). Coupling of Fc-COOH (1) and Boc-Fca (10) with "dipeptide" 9 resulted in the formation of Fc-CO-AlaAlm (12) and the trisamide Boc-Fca-Ala-Alm (13), respectively (Fc = ferrocenyl, Fca = 1Ј-aminoferrocene-1-carboxylic acid). The reactions were accomplished by the HOBt/EDC procedure, and the products were obtained in good yields [HOBt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…Classical hydrogen bonds between electronegative elements are important in secondary structures of natural peptides as well as in catalysis. , However, also nonclassical hydrogen bonds such as XH···M and XH···HM play a significant role in modern chemistry, especially in organometallics with rather electron rich metal centers. Organometallic peptides with conventional hydrogen bond forming ingredients, such as amino acids, sugars, ureas, , and lactams, based on classical hydrogen bonds , have been extensively studied and exploited. Molecular wires, redox-responsive foldamers, optically switchable valence tautomers, , porphyrin tweezers, and anion sensors have been devised from the combination of ferrocene and hydrogen bonds in organometallic systems.…”
Section: Introductionmentioning
confidence: 99%
“…Classical hydrogen bonds between electronegative elements are important in secondary structures of natural peptides as well as in catalysis. , However, also nonclassical hydrogen bonds such as XH···M and XH···HM play a significant role in modern chemistry, especially in organometallics with rather electron rich metal centers. Organometallic peptides with conventional hydrogen bond forming ingredients, such as amino acids, sugars, ureas, , and lactams, based on classical hydrogen bonds , have been extensively studied and exploited. Molecular wires, redox-responsive foldamers, optically switchable valence tautomers, , porphyrin tweezers, and anion sensors have been devised from the combination of ferrocene and hydrogen bonds in organometallic systems.…”
Section: Introductionmentioning
confidence: 99%
“…[13] By condensation of ferrocene acetyl chloride with 2-azetidinones substituted by a residue of alanine at the C3-position several b-lactam-containing ferrocene peptides have been prepared and their conformational properties were studied. [14] The macrocyclic bis-b-lactams 5, containing embedded Pd and Pt square-planar centers, were synthesized by the stepwise building of a bis-azetidinone system, having both rings tethered by an aliphatic chain, and the lactam nitrogen atom substituted by the terminal pyridine moieties 6. [15] Reaction of compounds 6 with cis-[M(dppe)(OTf) 2 ] (M= Pd, Pt, dppe = 1,2bis(diphenyl-phosphino)ethane, Tf = triflate) in the presence of NaOAc formed the diastereomerically pure metallic cavities 5 in essentially quantitative yields (Scheme 4).…”
Section: Incorporation Of the Metal In A Preformed B-lactammentioning
confidence: 99%
“…DFT calculations by Heinze and Rapić showed that the "Herrick" pattern is more stable than the "van Staveren" or "Xu" patterns. [14] P-and M-Helical conformations, which are interconvertible, based on a torsional twist about the Cp(centroid)-FeÀ Cp-(centroid) axis are present in the 1,n'-disubstituted ferrocene (Figure 5). [2] The introduction of the peptide chains, which have hydrogen bonding sites and chiral centers, into the ferrocene organometallic scaffold is expected to induce the helical chirality of the 1,n'-disubstituted ferrocene moiety by restriction of the torsional twist through the formation of intramolecular hydrogen bonds between the introduced chiral peptide chains.…”
Section: Introductionmentioning
confidence: 99%